Cumulative advantages and disadvantages in attainment of higher education: Set-analytic comparison of asymmetric inequalities in six European countries. (April 2022) - Lauri, Triin; Saar, Ellu
This article explores how parental resources work together to secure higher education for their offspring. It does so by, first, mapping the linkages between cumulative advantages and disadvantages of respondents' parental resources and educational attainment across countries and cohorts. Second, investigating under which institutional setup of education systems these linkages between parental background and educational attainment are the weakest. At both levels, the set-analytic approach is applied. We show that disadvantages tend to cumulate to a much greater extent than advantages and their role in hindering higher educational attainment is much stronger than advantages to enable it. The only configuration of educational system that is sufficient to mitigate linkages between cumulative background and educational attainment in both directions, that is, advantageous background to enable and disadvantageous background to hinder higher educational attainment, combines high levels of standardization and decommodification.